Uji Kinerja Mesin Penggiling Buah Pepaya Afkir - Kuncoro, Sapto; Tamrin, Tamrin; Kurniawan, Yoni (Jurnal Agricultural Biosystem Engineering, 2022)
Waste has long been a serious problem in various big cities in Indonesia. Garbage at this time has become a common problem that can disrupt the environment. Garbage piles will increase along with the increase in population. Papaya fruit is a fruit that is easily rotten and physically damaged because of the soft skin and flesh, according to the results of a survey I did, waste papaya fruit in the Natar market in South Lampung and the yellow bamboo market in Bandar Lampung as much as 10% and from papaya farmers as much as 20 %. Papaya fruit waste can be used as compost and as animal feed ingredients, one of which is BSf larvae. BSF fly larvae is one phase of the insect cycle where BSF fly larvae can be used as fish and poultry feed, BSF fly larvae can be given to fish and poultry alive and fresh, frozen, dried and paste, this grinding machine has been made by the author 2 years ago, Therefore the author conducted a performance test with papaya fruit at different levels of ripeness and different diameters of the sieve holes. The purpose of this study was to determine the performance of the papaya fruit grinder and to determine the results of grinding using 3 different sieves and the level of ripeness of papaya fruit. The method used in this study was factorial Randomized Block Design (RBD), then the data were analyzed using an analysis of variance (Anova) which was then further tested with the LSD test with the help of the SAS application. Keywords: BSF Fly Larvae, Garbage, Grinding Machine, Papaya, Waste.